Efforts to Foster Enthusiasm and Independence in Learning Mushroom Material in the Middle of the Covid-19 Pandemic with the Limbate-Based Assignment Method for Class X Science 1 Students for the 2021-2022 Academic Year at SMA N 4 Jayapura - Widowati, Rosa Reny (Universitas Syiah Kuala, 2024)
This study aims to find out whether the Limbate-based assignment method can foster enthusiasm and independence in learning Mushroom material in grade X Science 1 students at SMA Negeri 4 Jayapura. To foster students' enthusiasm and independence in learning Mushroom material during the COVID-19 pandemic, learning innovations were carried out by applying the Limbate-based assignment method (Material Reading Literacy). The Limbate-based assignment method was carried out in two meetings. The science literacy material used is deliberately prepared by the teacher and shared with students so that there is equal information received by students so that they can do the same assignment from the teacher. After action with the Limbate-based assignment method, changes in cognitive, affective, and psychomotor abilities were seen classically. Cognitive ability from 70% (sufficient) to 92% (very good), affective ability from 74% (medium) to 86% (high), and psychomotor ability from 65% (medium) to 78% (high). From the results of this data processing, actions with the Limbate-based assignment method can foster students' enthusiasm and independence in learning Mushroom material.